2011
DOI: 10.1590/s0100-40422011000700026
|View full text |Cite
|
Sign up to set email alerts
|

Análise de pesticidas organoclorados em água usando a microextração em fase sólida por headspace com cromatografia gasosa e espectrometria de massas

Abstract: Recebido em 2/9/10; aceito em 16/2/11; publicado na web em 15/4/11 ANALYSIS OF ORGANOCHLORINE PESTICIDES IN WATER USING HEADSPACE SOLID PHASE MICROEXTRACTION WITH GAS CHROMATOGRAPHY AND MASS SPECTROMETRY. A method based on headspace -solid phase microextraction coupled with gas chromatography -mass spectrometry was validated for the quantitative determination of 18 organochlorine pesticides in water. For the extraction conditioning some parameters as the best type of coating fiber, time and temperature of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results of this study, shown in Figure 2, indicate a reduction in the extraction efficiency of the OCPs when the ionic strength was increased. This finding is in agreement with that reported by Dong [7] , Prates [8] and Pawliszyn [9,10,11] who studied the salting out effect on the extraction of OCPs. Therefore, no salt was added to the vials for the next steps of this study.…”
Section: Optimization Of Extraction Conditionssupporting
confidence: 93%
“…The results of this study, shown in Figure 2, indicate a reduction in the extraction efficiency of the OCPs when the ionic strength was increased. This finding is in agreement with that reported by Dong [7] , Prates [8] and Pawliszyn [9,10,11] who studied the salting out effect on the extraction of OCPs. Therefore, no salt was added to the vials for the next steps of this study.…”
Section: Optimization Of Extraction Conditionssupporting
confidence: 93%
“…The DVB/Car/PDMS was selected to continue this study because it presented better performance for the extraction of Į-BHC. Also, other authors in the literature describe the DVB/Car/PDMS as the best fiber for the analysis of OCPs [19,20].…”
Section: Optimization Of Commercial Fibermentioning
confidence: 99%
“…However, considering the size of the country and the total amounts of pesticides applied, the number of studies describing pesticides in surface water [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and in ground water [16][17][18][19][20][21][22][23][24][25] is not large. Most of these studies have examined organochlorine pesticides, most of which have been banned in Brazil since the 1980s, except for endosulfan, which will be prohibited beginning in 2013.…”
Section: Introductionmentioning
confidence: 99%